Naltrexone-Induced Cardiac Function Improvement is Associated With an Attenuated Inflammatory Response and Lipid Perioxidation in Volume Overloaded Rats - Dehe, Lukas; Mousa, Shaaban A.; Shaqura, Mohammed; Shakibaei, Mehdi; Schäfer, Michael; Treskatsch, Sascha (Frontiers in Pharmacology, 2022)
In previous studies, upregulation of myocardial opioid receptors as well as the precursors of their endogenous ligands were detected in the failing heart due to chronic volume overload. Moreover, opioid receptor blockade by naltrexone improved left ventricular function. In parallel, inflammatory processes through cytokines have been confirmed to be an important contributing factor to the pathogenesis of different forms of heart failure. Thus, the present study examined the systemic inflammatory response to chronic volume overload and its modulation by chronic naltrexone therapy. Chronic volume overload was induced in male Wistar rats (n = 8) by applying an infrarenal aortocaval fistula (ACF) for 28 days during which the selective opioid receptor antagonist naltrexone (10 mg × kg-1 × h-1) or vehicle was administered via a subcutaneously implanted Alzet minipump. The ultrastructural, morphometric and hemodynamic characterization of ACF animals were performed using an intraventricular conductance catheter in vivo and electronmicroscopy in vitro. Co-localization of mu-, delta- and kappa-opioid receptors with voltage gated L-type Ca2+ channels in cardiomyocytes as well as IL-6, IL-12, TNF-alpha, and Malondialdehyde (MDA) plasma concentrations were determined by ELISA. In rat left ventricular myocardium, mu-, delta- and kappa-opioid receptors colocalized with voltage gated L-type Ca2+ channels and mitochondria in left ventricular cardiomyocytes. In rats with ACF-induced volume overload, signs of heart failure and myocardial ultrastructural damage, chronic naltrexone therapy improved cardiac function and reversed the increased inflammatory cytokine expression as well as lipid peroxidation. In conclusion, our results provide evidence of a cardiodepressant effect of the intrinsic cardiac opioid system during chronic volume overload. This was accompanied by an increased expression of systemic inflammatory cytokines as well as lipid peroxidation. Antagonism of the intrinsic opioid receptor activation by chronic naltrexone improved cardiac function, reduced the enhanced expression of inflammatory cytokines and lipid peroxidation.